The effects of different personal data categories on information privacy concern and disclosure. Issue 110 (November 2021) - Chua, Hui Na; Ooi, Jie Sheng; Herbland, Anthony
Abstract: The potential threats of exposing personal data associated with online services have been a reason for concern, and individuals as customers may decline to disclose their data due to trust issues. Literature has shown evidence that greater transparency in the types and purposes of data requested encourages individuals to disclose personal data. This evidence indicates a need to examine the characteristics of personal information practices. Furthermore, current data privacy regulations recognize the presence of different data characteristics such as location-specific, health-specific, and financial-specific. Yet, current legislations are formed to identify personal data as a singular category regardless of the requirements, including the specification of processed personal data to be relevant and limited to what is necessary for enabling service functions. Without categorization, measuring "relevant" and "necessary" can be ambiguous. Several pieces of researches have explored the impact of personal information type and sensitivity level on privacy concern and disclosure; however, most of them lacked an in-depth examination of data categorization with systematic validation. Our study aims to fill this gap, and additionally further look into how contextual demographic factors influence the perception on information privacy concern and disclosure of different personal data categories from a Malaysian perspective. Our study provides new evidence of validated personal data categories and their significant differences in perceived information privacy concern and disclosure intention. Our research finding also discovers that Age, Gender, and Working Industry, as demographic factors, have significant effects on disclosure intention associated with Tracking, Finance, Authenticating, and Medical-health information.